2019
DOI: 10.5785/34-2-807
|View full text |Cite
|
Sign up to set email alerts
|

Information communication technologies as a support strategy for learners experiencing reading difficulties

Abstract: One of the most significant current discussions in education departments around the world is reading difficulties. This article explores the use of information communication technologies (ICTs) to support learners experiencing reading difficulties in two public primary schools. For data collection purposes, a total of 18 school-based support team members and two learning support educators participated in this research through focus group interviews and observation. From the data collected, the teachers' percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In his international review, McEwan (2015) found that computerassisted learning was associated with the highest impact on general learning outcomes. From our South African Review, Mphahlele and Nel (2018) argued ICTs work well in identifying learners' reading difficulties and reading levels and that they are useful tools in promoting the literacy development of those experiencing difficulties. However, there are numerous challenges involved in this strategy, including equitable access.…”
Section: Pointers For Successful Interventions Teaching Pedagogiesmentioning
confidence: 99%
“…In his international review, McEwan (2015) found that computerassisted learning was associated with the highest impact on general learning outcomes. From our South African Review, Mphahlele and Nel (2018) argued ICTs work well in identifying learners' reading difficulties and reading levels and that they are useful tools in promoting the literacy development of those experiencing difficulties. However, there are numerous challenges involved in this strategy, including equitable access.…”
Section: Pointers For Successful Interventions Teaching Pedagogiesmentioning
confidence: 99%
“…Although, Mouter (2012) acknowledges intercoder reliability when manual coders are used instead of utilising text software such as Atlas-ti, we argue that as long as two different researchers coded the same body of content and generated similar codes, the codes are reliable. We also used Cohen's kappa coefficient as emphasised by Mphahlele (2018) to measure intercoder reliability. All the codes in Table 1 show strong intensity because Cohen's kappa coefficient levels of intensity are the following: (0) = no mention -the theme is not expressed in any way;…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The acquisition of literacy skills is consequently negatively affected, as English additional language learners typically display reduced speech and language skills as well as inadequate reading and spelling abilities (Geertsema & Le Roux 2014). It can be argued that their proficiency in English has not developed sufficiently to ensure optimal academic performance (Mphahlele & Nel 2018). Professionals working in the field of SLD (DD) should have adequate knowledge about the nature of the condition and its management, as they play an important role in assisting the affected children.…”
Section: Introductionmentioning
confidence: 99%